STRATEGI BIMBINGAN BACA TULIS AL-QURAN (BTQ) MELALUI METODE JIBRIL BAGI SISWI KELAS X SMA AL-RIFAIE GONDANGLEGI MALANG. - Luluk Azizah; Nur Hasan; Lia Nur Atiqoh Bela Dina (VICRATINA, 2020)
For a Muslim has an obligation to study the Qur'an and practice the purpose of research that describes the learning process of writing Al-Quran (BTQ) through the method of Gabriel in SMA Al-Rifaie, describing the implementation of read-Quran (BTQ) study through the Gabriel method in Sma al-Rifaie, describing the implementation of the study of al-Quran writing (BTQ) through the method of Gabriel in Sma al-Rifaie. According to the analysis of data that is found, it can be known planning the learning of the Quran through the method of Gabriel in SMA Al-Rifaie divided into classes that are adapted to the students ' division, there is a target of learning and sharing time allocation, as well as an individual deposit system that is carried out at the end of the meeting every day . The conclusion of this researcher shows the method of Gabriel is a method of reading Quran by way of educators to read the verse one paragraph or waqaf in accordance with the order of Alloh is Tarteel, with two stages Tarqiq and tarteel corresponding to Makhorj and Tajwidnya then the student impersonate Taqliq teacher readings according to the model.